HUBUNGAN KUALITAS INFORMASI PADA KANAL YOUTUBE YULIA BALTSCHUN DENGAN SIKAP SUBSCRIBERS - Hilwah Hafidzah Muthmainnah; Wina Erwina; Andri Yanto (Shaut Al-Maktabah : Jurnal Perpustakaan, Arsip dan Dokumentasi, 2023)
This research based on the many users and information that available on YouTube, one of which is diet YouTuber called Yulia Baltschun. Yulia is a diet influencer with 2.5 million subscribers who provides diet information with interesting explanations and refutations of many diet myths. This study aims to determine the correlation between the quality of information on Yulia Baltschun's YouTube channel, by the indicators are accuracy, timeliness and relevance of information with subscribers’s attitude. Researchers used quantitative research methods by distributing questionnaires to 100 samples determined by purposive sampling. The data analysis technique used is descriptive analysis and inferential statistics. The population in this research is Yulia Baltschun's YouTube channel subscribers. The results of this study indicate that there is a significant positive relationship between the qualities of information on Yulia Baltschun's YouTube channel with subscribers’s attitude. Based on the results of Rank Spearman's correlation analysis, it shows that the quality of information on Yulia Baltschun's YouTube channel has a very strong affinity with a correlation coefficient is 0.722. In addition to each indicator, accuracy has a strong correlation with a correlation coefficient is 0.546, timeliness has a moderate correlation with a correlation coefficient is 0.470, and information relevance has a strong correlation with a correlation coefficient is 0.689. It can be concluded that Yulia Baltschun's YouTube channel has quality information with accurate, timely, and relevance indicators related with subscribers’s attitude.